'THE GRAVE OF THE COURT PIT': A REDISCOVERED BRONZE AGE TOMB FROM CARCHEMISH. (March 2014) - Sconzo, Paola
<x content-type="archive" xml:space="preserve">Abstract</x> This paper examines the British Museum unpublished records related to an Early Bronze (EB) Age pithos burial uncovered a century ago in the Inner Town at Carchemish. The grave, cursorily cited and variously dated (Chalcolithic, EB or even LBA) in the final reports, was described in some detail by Hogarth and Thompson; a precise dating is, however, possible today thanks to the information of paramount importance given by T. E. Lawrence who identified and took a picture of the associated finds, which was recently rediscovered in the Carchemish Archives. The pithos can be now ascribed to the third quarter of the third millennium BC and helps to confirm the recent theory according to which the Inner Town of Carchemish, with its massive earthen rampart, had already developed at the time of the second urbanisation in Syria and upper Mesopotamia.